Arabidopsis phosphoribosylanthranilate isomerase: molecular genetic analysis of triplicate tryptophan pathway genes. - Li, J (1995)
Phosphoribosylanthranilate isomerase (PAI) catalyzes the third step of the tryptophan biosynthetic pathway. Arabidopsis PAI cDNAs were cloned from a cDNA expression library by complementation of an Escherichia coli trpC- PAI deficiency mutation. Genomic DNA blot hybridization analysis detected three nonallelic genes encoding PAI in the Arabidopsis genome. DNA sequence analysis of cDNA and genomic clones indicated that the PAI1 and PAI2. All three PAI polypeptides possess an N-terminal putative plastid target sequence, suggesting that these enzymes all function in plastids. The PAI1 gene is flanked by nearly identical direct repeats of approximately 350 nucleotides. Our results indicate that, in contrast to most microorganisms, the Arabidopsis PAI protein is not fused with indole-3-glycerolphosphate synthase, which catalyzes the next step in the pathway. Yeast artificial chromosome hybridization studies indicated that the PAI2 gene is tightly linked to the anthranilate synthase alpha subunit 1 (ASA1) gene on chromosome 5. PAI1 was mapped to the top of chromosome 1 using recombinant inbred lines, and PAI3 is loosely linked to PAI1. cDNA restriction mapping and sequencing and RNA gel blot hybridization analysis indicated that all three genes are transcribed in wild-type plants. The expression of antisense PAI1 RNA significantly reduced the immunologically observable PAI protein and enzyme activity in transgenic plants. The plants expressing antisense RNA also showed two phenotypes consistent with a block early in the pathway: blue fluorescence under UV light and resistance to the anthranilate analog 6-methylanthranilate. The extreme nucleotide conservation between the unlinked PAI1 and PAI2 loci suggests that this gene family is actively evolving.